2016
DOI: 10.1007/s12262-016-1463-4
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Scrotal Calcinosis

Abstract: Idiopathic scrotal calcinosis (ISC) is a rare benign condition which presents with multiple, asymptomatic, and painless nodules on the scrotal skin wall. The lesions have been attributed as sebaceous cysts, calcified steatocystoma, fibroma, atheroma, and xanthoma. Shapiro et al. reviewed the histologic data and found no evidence of an epithelial lining, residual cysts, and lipid or organisms, and concluded that the calcification was idiopathic introducing the term "idiopathic scrotal calcinosis." We have studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The latter is designated idiopathic scrotal calcinosis. The major difference to calcified cysts is the complete absence of a lining epithelium [ 3 ]. Surgery is the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is designated idiopathic scrotal calcinosis. The major difference to calcified cysts is the complete absence of a lining epithelium [ 3 ]. Surgery is the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we report a rare case of extensive ISC. It affects dark‐colored skin men aged from 20–40 years old, suggesting an ethnic susceptibility 1 …”
Section: Presentationmentioning
confidence: 99%
“…Our Differential diagnosis was: -Scrotal Sebaceous Cysts -Scrotal Malignancy -Calcified Steatocystoma [2] Based on the patient history and our deferential diagnosis, we booked the patient for surgery as an outpatient day care case surgery for removal of the scrotal nodules. Under general anesthesia, we did elliptical incisions and some of the nodules we did e nucleation, we removed all the nodules which were nine in number.…”
Section: Case Reportmentioning
confidence: 99%
“…Shapiro et al reviewed the histologic data and found no evidence of an epithelial lining, residual cysts, lipid or organisms, and concluded that the calcification was idiopathic introducing the term "idiopathic scrotal calcinosis [2].…”
Section: Introductionmentioning
confidence: 99%